Влечение: [повесть] / Елена Усачева - Усачева Елена Александровна (Пленники сумерек, 2009)
Экземпляры: ф.8 (2020) / Инвентарный номер: 56097 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: У 74 / ББК: 84(2Рос=Рус)6